Advertising in digital television - Sádaba, Charo (Javnost (Ljubljana), 2002)
Over the last decade, the Spanish television market has radically changed, buttelevision has never ceased being a favourite medium for advertisers, not only because of its potential to communicate emotions with a unique touch but above all because it reaches 98 per cent of Spanish households. In recent years, consumption of television has increased in Spain, now on the digital threshold, and there is already evidence from the US that households with access to fully interactive digital television increase their overall consumption of the medium. And yet, Infoadex data on advertising spend in Spain during 2001 indicates that out of the 18% of the total media investment received by television, less than 1.7% of that was spent on digital television. This raises an important question: why does advertiser interest indigital television not grow at the same pace as audience acceptance of the new technology? The arrival of digital multichannel television in 1997 means we must reconsider the concept of advertising in a medium in which the user pays for access to content. Advertising must now focus on becoming an added value service for the viewer, augmenting programme content. Digital televisionhas the ability to increase segmentation of the audience and its interactive possibilities open the way towards creating new advertising messages. This paper explores the response of advertisers and other professional actors across the media sector. Its object is to establish an initial analysis of the reasons for the inhibited attitude of advertisers towards digital television. After a brief review of the present situation in Spain - with reference to the business models and the legal framework in whichdigital television is developing - we examine the role of advertising, using interviews with different professionals in the field, in order to identify the main barriers to advertising investment in digital television.
Keywords: Spain; Španija; television; televizija; digital television; digitalna televizija; reklama; advertising; oglaševanje